PENGEMBANGAN MEDIA MYSTERY BOX MATERI WARISAN BUDAYA TERHADAP HASIL BELAJAR KOGNITIF SISWA KELAS V - Afrilia Serawati, Chika; Asnawati, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low interest and learning outcomes of fifth grade students of SDN Wanacala on Cultural Heritage material in the Natural and Social Sciences (IPAS) subject. Learning that is still dominated by conventional methods tends to be less able to attract students' attention, resulting in decreased motivation and enthusiasm in participating in the learning process. To overcome these problems, this study aims to develop Mystery Box media on Cultural Heritage material for fifth grade elementary school students and evaluate its effectiveness in improving students' cognitive learning outcomes. The research employed the Research and Development (R&D) method with the ADDIE development model, encompassing Analysis, Design, Development, Implementation, and Evaluation stages. The subjects were fifth-grade students at SDN Wanacala. Data collection instruments included media and material expert validation sheets, student and teacher response questionnaires, and learning outcome tests. The results indicated that the developed Mystery Box media was categorized as highly feasible, with validation scores of 95.4% from media experts and 91.4% from material experts. Positive responses were also shown by teachers and students, with percentages of 93.8% and 88.8%, respectively. Paired Sample T-Test analysis yielded a significance value of 0.000, indicating a significant difference between pretest and posttest scores. N-Gain calculations showed an improvement in learning outcomes within the medium category, specifically 0.688 for large scale. Therefore, the Mystery Box media is effective and suitable for use in teaching the Cultural Heritage material in IPAS to enhance the cognitive learning outcomes of fifth-grade students at SDN Wanacala.